2019
DOI: 10.1155/2019/8456342
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Topographic Parameters on the Adhesion and Proliferation of Human Gingival Fibroblasts and Oral Bacterial Strains

Abstract: Dental implantology allows replacement of failing teeth providing the patient with a general improvement of health. Unfortunately not all reconstructions succeed, as a consequence of the development of infections of bacterial origin on the implant surface. Surface topography is known to modulate a differential response to bacterial and mammalian cells but topographical measurements are often limited to vertical parameters. In this work we have extended the topographical measurements also to lateral and hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…The size of certain bacterial strains such as P. gingivalis is substantially smaller than that of cells, and their attachment may be affected by nanoroughness. For instance, Pacha-Olivenza et al reported that an increase in nanoroughness stimulated bacterial metabolism in vitro [35,44]. Similar findings have been reported by Singh et al, who indicated that surface roughness (<20 nm) accelerated bacterial adhesion and that increasing the surface roughness (>32 nm) reduced bacterial adhesion [45].…”
Section: Discussionsupporting
confidence: 55%
“…The size of certain bacterial strains such as P. gingivalis is substantially smaller than that of cells, and their attachment may be affected by nanoroughness. For instance, Pacha-Olivenza et al reported that an increase in nanoroughness stimulated bacterial metabolism in vitro [35,44]. Similar findings have been reported by Singh et al, who indicated that surface roughness (<20 nm) accelerated bacterial adhesion and that increasing the surface roughness (>32 nm) reduced bacterial adhesion [45].…”
Section: Discussionsupporting
confidence: 55%
“…In a recent study, researchers compared cell adhesion of human fibroblasts and three bacteria species involved in infection of oral implants as a function of surface roughness. Results showed the behavior of fibroblasts and bacteria is quite dissimilar, probably because mammalian cells and bacteria have different attachment strategies (Pacha‐Olivenza et al, 2019). Based on the result of this study, we were unable to generate a predictive model that relate micropatterns to metabolic activity and alignment of the SCs and fibroblasts conceivably because mammalian cell responses are more complicated than those of bacteria and highly sensitive to the microenvironmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Polyimide is not as ubiquitous as polydimethylsiloxane elastomers for the fabrication of engineered microtopographies; however, fabrication techniques are available and were used previously (Kuliasha & Judy, 2018). In addition, the fabrication methods used in this study are fully compatible with standard microfabrication protocols and can easily be applied to polyimide nerve interface device fabrication (Ordonez, Boehler, Schuettler, & Stieglitz, 2012). Microtopography size and spacings for both channels and Sharklet™ were chosen to range from 2 to 20 μm, which is comparable to the size range of the SCs and fibroblasts.…”
mentioning
confidence: 99%
“…Furcation areas present some of the greatest challenges of the success of periodontal therapy [ 4 ]. It has been demonstrated that many variables could alter the oral environment, such as the presence of osseointegrated implants [ 6 ], orthodontic appliances [ 7 ], or topographic hard-to-reach areas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%